Penggunaan Teknologi Multimedia Pada Pembelajaran Literasi Anak Usia Dini Pada TKIT Ilmi Khoir - ., Suwinda Aulansari; ., Dara Amelia; ., Ade Risky Pradika; ., Ali Ikhwan (CV. ITTC INDONESIA, 2022)
The purpose of this study is to define the use of multimedia technology in literacy learning in early childhood, including the implementation of the use of multimedia technology in literacy learning in children aged 5-6 years. This research method uses qualitative research. Interview techniques and document reviews are used in the collection of information. The validity of the data is obtained by data triangulation. Data analysis techniques are carried out with interactive models. The results of the study proved that: the application of the use of multimedia technology in literacy learning shows that learning becomes more conducive and directed. By utilizing multimedia technology, children become easier to understand learning and learning becomes more effective.